O documentário perfurado: Um estudo sobre as possibilidades de abertura e expansão do filme/vídeodocumentário - Andre Hallak M Costa C G de Oliveira (2009)
This dissertation investigates the constant artistic concepts crossing-over and also investigates practices in the film/videodocumentary field. The nuances of this crossing-over are manifested in different contexts and in different ways, highlightingthe potential of the documentary genre to self-questioning through the disassembly and testing of its own language. For this matter, historical aspects of the documentary genre are investigated by also using some conceptual tools to emphasize the thinking of Gilles Deleuze on moving images. Films and videos are an important reference for the matters of this study and therefore are used to demonstrate how the hybridism appears in the very heart of the filmic and videographic practices. The same films and videos are also used to dismantle the classical categories of documentary, toward the vast possibilities of the drilleddocumentary.